Whole-Body Synergy-Based Balance Control for Quadruped Robots with Manipulators on Sloped Terrains - Ru Kang; Huifeng Ning; Fei Meng; Zewen He (Cyborg and Bionic Systems)
A quadruped robot with a manipulator that combines dynamic motion and manipulation capabilities will greatly expand its application scenarios. However, the addition of the manipulator raises the center of mass of the quadruped robot, increasing complexity in motion control and posing new challenges for maintaining balance on sloped terrains. To address this, a balance control method based on whole-body synergy is proposed in this study, emphasizing adaptive adjustment of the robot system’s overall balance through effective utilization of the manipulator’s active motion. By establishing a mapping relationship between the manipulator and the robot’s attitude angle under system equilibrium, the desired manipulator motion is guided by real-time estimates of terrain angles during motion, enhancing motion efficiency while ensuring robot balance. Furthermore, to enhance motion tracking accuracy, the optimization of system angular momentum and manipulator manipulability is incorporated into hierarchical optimization tasks, improving manipulator controllability and overall system performance. Simulation and experimental results demonstrate that the quadruped robot with a manipulator exhibits reduced velocity and attitude angle fluctuations, as well as smoother foot-end force dynamics during climbing motions with the addition of manipulator adaptive adjustment. These results validate the effectiveness and superiority of the manipulator-based adaptive adjustment strategy proposed in this paper.